Anthropogenic impact on the microbiota of seashore and freshwater environments in Northern and Eastern Iceland : preliminary assessment and surfactant-degrader bioprospecting - María Markúsdóttir (2011)
Verkefnið er lokað Although generally reputed pure and uncontaminated, most Icelandic aquatic environments are to some degree anthropogenically impacted, especially those neighbouring urban areas and small-scale settlements. In the present study, two types of aquatic environments were surveyed; three wastewater-exposed seashore environments and a freshwater system comprising the river Glerá and its watershed. Three Icelandic seashore areas were sampled; Ólafsfjörður in North-Iceland, Reyðarfjörður in the East and Hvammstangi in the North-Western part. These environments are subject to wastewater discharges from nearby municipalities and shipping activities. The widespread and copious usage of several types of cleaning detergents and other surfactants results in their relatively high concentrations in both domestic and industrial sewage, which enters the aquatic environment untreated in most Icelandic localities. The river Glerá in Northern Iceland presents a convenient system for evaluating the effects of anthropogenic activities on microbial communities. The river originates in pristine surroundings and then flows past a local landfill and through an urban area, receiving inflows from various small-scale industries. Samples from the two environmental types were screened for surfactant-degrading activity and surfactant biodegraders isolated. All of the degrading isolates were found to belong to the class Gammaproteobacteria. In the freshwater system, surfactant degraders solely comprised pseudomonads, while the species composition was more diverse in the seashore samples. The seashore was generally found to be a poor source of surfactants degraders. The river environment was also screened for the appearence of mercury-tolerant bacteria, as an indicator of the degree of environmental pollution. It was found that the landfill leachate had an impact on the river microbiota downstream. Mercury resistance was markedly increased, as well as species diversity, determined by partial 16S rRNA sequencing.